Boron alleviates the aluminum toxicity in trifoliate orange by regulating antioxidant defense system and reducing root cell injury. (15th February 2018) - Riaz, Muhammad; Yan, Lei; Wu, Xiuwen; Hussain, Saddam; Aziz, Omar; Wang, Yuhan; Imran, Muhammad; Jiang, Cuncang
Abstract: Aluminium (Al) toxicity is the most important soil constraint for plant growth and development in acid soils (pH < 5.5) globally in agricultural regions. Boron (B) is an essential micronutrient for the growth and development of higher plants. The results of previous studies propose that B might ameliorate Al toxicity; however, none of the studies have been conducted on trifoliate orange to study this effect. Thus, a study was carried out in hydroponics comprising of two different Al concentrations, 0 and 400 μM. For every concentration, two B treatments (0 and 10 μM as H3 BO3 ) were applied to investigate the B-induced alleviation of Al toxicity and exploring the underneath mechanisms. The results revealed that Al toxicity under B deficiency severely hampered the root growth and physiology of plant, caused oxidative stress and membrane damage, leading to severe root injury and damage. However, application of B under Al toxicity improved the root elongation and photosynthesis, while reduced Al uptake and mobilization into plant parts. Moreover, B supply regulated the activities of antioxidant enzymes, proline, secondary metabolites (phenylalanine ammonia lyase and polyphenol oxidase) contents, and stabilized integrity of proteins. Our study results imply that B supply promoted root growth as well as defense system by reducing reactive oxygen species (ROS) and Al concentrations in plant parts thus B induced alleviation of Al toxicity; a fact that might be significant for higher productivity of agricultural plants grown in acidic conditions. Highlights: Boron (B) supply improves root elongation under Al toxicity. B supply eliminates oxidative stress and Al induced root cell injury by regulating antioxidant defense system. The B-induced alleviation of Al toxicity might be associated with the reduced uptake of Al.